Exploration of the cellular effects of the high-dose, long-term exposure to coffee roasting product furan and its by-product cis-2-butene-1, 4-dial on human and rat hepatocytes. (1st September 2020) - Teodoro, João S.; Silva, Rui; Aguiar, António; Sobral, Abílio J. F. N.; Rolo, Anabela P.; Palmeira, Carlos M.
Abstract: Coffee is the most popular hot beverage and caffeine is the most used psychoactive drug in the world. Roasting of coffee beans leads to the generation of minute quantities of undesirable compounds, such as furan. It is now thought that the toxicity of furan derives from its processing by CYP450 family of detoxifying enzymes, leading to the formation of cis -2-butene-1, 4-dial (BDA). BDA has known cytotoxicity capacities, binding to proteins, nucleic acids, and glutathione (GSH). BDA also appears to mediate furan's toxic effects, since the inhibition of CYP450 family impedes the aforementioned toxicological effects of furan. There are some studies performed on furan's toxicity, but very few on BDA. Furthermore, the doses used in these studies appear to be fairly high when compared with the expected dosage one could be exposed to in a standard day. As such, to understand if furan and BDA could have toxic effects using more realistic doses and longer time frames, human and rat hepatocytes were exposed to furan or BDA for up to 96 h,  and several biochemical parameters were assessed. We report here that human hepatocytes were more sensitive than rat's, in particular to furan, for we show a decrease in MTT reduction, ATP levels and increase in carbonyl formation and 8-OHdG accumulation in the longer time points. BDA was mostly ineffective, which we attribute to a low import rate into the cells. In conclusion, we show that there is potential for harm from furan in high doses, which should be carefully addressed.